PERAN ORANG TUA DAN SEKOLAH DALAM MEMBENTUK MINAT BACA SISWA - Munfaridah, Nisa Arifatul; Amaruddin, Hidar (Universitas Negeri Medan, 2023)
Abstract: The Role of Parents and Schools in Shaping Students' Reading Interest. The purpose of this study was to determine how the role of parents and schools in shaping students' interest in reading. This type of research is a case study qualitative method. The informants in this study were two second grade students, two second grade parents, a second grade teacher, and the principal of SD NU Pemanahan. The data collection techniques used in this research are interviews, observation, and documentation. The results of this study indicate that the importance of the role of parents and schools in shaping reading interest through indicators of the role of parents (educators, encouragers, facilitators and mentors), the role of the principal (setting policies, running agendas, strengthening relationships with parents, and ensuring success), and the role of teachers (educators, role models, learning resources and facilitators) with parenting activities set by the principal based on the foundation of Albert Bandura's social learning theory to create a school atmosphere that supports the formation of students' reading interest. However, the implementation of the policy needs to be improved to ensure the set goals can be achieved. Therefore, there is a need for joint evaluation and review from parents, principals and teachers to achieve this goal.Keyword: Parental Role, School Role, Reading Interest.Abstrak: Peran Orang Tua dan Sekolah dalam Membentuk Minat Baca Siswa. Tujuan penelitian ini untuk mengetahui bagaimana peran orang tua dan sekolah dalam membentuk minat baca siswa. Jenis penelitian ini adalah metode kualitatif studi kasus. Informan dalam penelitian ini adalah dua siswa kelas dua, dua orang tua kelas dua, guru kelas dua, dan kepala sekolah SD NU Pemanahan. Teknik pengumpulan data yang digunakan dalam penelitian ini berupa wawancara, observasi, dan dokumentasi. Hasil penelitian ini menunjukan bahwa begitu pentingnya peran orang tua dan sekolah dalam membentuk minat baca melalui indikator peran orang tua (pendidik, pendorong, fasilitator dan pembimbing), peran kepala sekolah (menetapkan kebijakan, menjalankan agenda, mempererat hubungan dengan orang tua, dan menjamin keberhasilan), serta peran guru (pendidik, panutan, sumber belajar dan fasilitator) dengan kegiatan parenting yang ditetapkan oleh kepala sekolah berdasarkan landasan dari teori belajar sosial dari Albert Bandura untuk menciptakan suasana sekolah yang mendukung terbentuknya minat baca siswa. Namun implementasi kebijakan tersebut perlu ditingkatkan untuk memastikan tujuan yang ditetapkan dapat tercapai. Oleh karena itu, perlu adanya evaluasi dan tinjauan ulang bersama dari orang tua, kepala sekolah, dan pihak guru untuk mencapai tujuan ini. .Kata Kunci: Peran Orang Tua, Peran Sekolah, Minat Baca